User engagement in social media - empirical results from Facebook. (3rd October 2019) - Rauniar, Rupak; Rawski, Greg; Salazar, Ronald J.; Hudson, Donald
Theory building and better understanding of user engagement behaviour are fundamental to developing future approaches and effective organisational deployment of social media technologies. Based on the theory of reasoned action (TRA), predictors of intention to engage on social media sites were empirically examined with 389 users of Facebook - the most popular online social media site. Our results suggest that perceived value, social presence, interactivity, and trustworthiness are positively related to the user's attitude towards social media. The research model shows promise for use by managers and organisations to predict and understand the usage of social media in a target population.